High tumor amplification burden is associated with TP53 mutations in the pan-cancer setting - Rushikesh S. Joshi; Amelie Boichard; Jacob J. Adashek; Razelle Kurzrock (Cancer Biology & Therapy, 2022)
Next-generation sequencing data is fundamentally changing the clinical management of patients with cancer. The most frequent genomic alterations in malignancy are mutations and amplifications, with a subset of tumors having multiple amplifications – “amplificators”. We sought to understand the molecular correlates of high tumor amplification burden in a pan-cancer context. Using both national registries and a single-institution dataset, our results demonstrate that cancers with TP53 mutations (as compared to those with wild-type TP53) exhibited significantly higher tumor amplification burden across all datasets. Amplifications, generally associated with overexpression, may be potentially actionable secondary consequences of TP53 mutations.